Preparation of Silica Modified with 2-Mercaptoimidazole and its SorptionProperties of Chromium(III) - Harry Budiman; H. K. Fransiska Sri; Achmad. H. Setiawan (E-Journal of Chemistry)
Modified silica gel was prepared to remove the heavy metal of chromium(III) from water sample. Silica gel was used as supporting material and the 2-mercaptoimidazole was immobilized onto surface silica so that the silica would have selective properties to adsorb the heavy metal chromium(III) through the formation of coordination compound between the 2-mercaptoimidazole and chromium(III). The characterization of modified silica gel was carried out by analyzing the Fourier Transform Infrared Spectrum of this material in order to ensure the immobilization of 2-mercaptoimidazole onto the surface. The effect of pH solution, initial concentration of chromium(III), and interaction time were investigated in batch mode to find the adsorption properties of chromium(III) onto modified silica. The condition optimum of these parameters was applied to determine the removal percentage of chromium(III) in water sample using the modified silica gel